Self-lubricating antifriction coating for bearing bush based on top layer of Ag layer as well as preparation method and application of self-lubricating antifriction coating
By depositing Ni gate layer, AlSn35Cu support functional layer and Ag friction reduction self-lubricating layer on the surface of the bearing shell, a composite coating material is formed, which solves the problems of high friction coefficient and poor occlusivity of the bimetal alloy bearing alloy layer, and the effect of reducing friction coefficient and improving occlusivity is achieved.
Patent Information
- Application Number
- CN202411911025.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing bimetal alloy bearing shells have high friction coefficient and poor occlusivity, resulting in a short service life.
A self-lubricating friction reducing coating based on the top layer of the Ag layer is used to form a composite coating material by depositing a Ni gate layer, an AlSn35Cu support functional layer and an Ag friction reducing self-lubricating layer on the surface of the bearing shell.
Significantly reduces the friction coefficient, improves anti-blocking performance, extends the service life of the bearing shells, and improves reliability under high load and high speed conditions.
Smart Images

Figure CN119710590A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of bearing bush coatings, and in particular to a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer, and a preparation method and application thereof. Background Art
[0002] Bimetallic bearing materials are currently in the international frontier research field. They are mainly composed of two materials, soft and hard, which are steel back support layer and alloy anti-friction layer. The alloy layer is mainly divided into babbitt alloy, copper-based alloy and aluminum-based alloy. However, its surface properties (such as friction and wear) are poor, and surface modification treatment is usually used to further improve it in order to improve the current performance of the bearing. In the early stage of the development of bearing coatings, electroplating layers were mainly used, such as tin (Sn), silver (Ag) and lead-tin-copper alloy (PbSn10Cu2) coatings, but they have poor durability and high wear during use, which causes a lot of noise and obvious vibration during operation, seriously reducing the service life of the diesel engine. With the development of high-speed diesel engines, the speed and power requirements of newly designed diesel engines are constantly increasing, and the expected value of service life is also increasing sharply, requiring the bearing coating to have significant improvements in mechanical properties and performance indicators. With the promotion of coating preparation technology and the increase in application demand, and in order to reduce environmental pollution during coating preparation, foreign institutions have successively developed solid lubricating coating technology, including the crystal structure and self-lubricating mechanism of graphite, soft metals, sulfides, fluorides and oxides, and studied single-layer, double-layer, multi-layer composite, nanostructured multi-layer and particle-reinforced toughening coating structures, and developed wear-resistant self-lubricating material preparation technologies such as powder metallurgy, magnetron sputtering, plasma spraying and laser pulse deposition. At present, due to reasons such as confidentiality of commercial information, there are few publicly published latest research results in this area. Therefore, the preparation of domestic solid lubricating coatings is still in the exploratory stage. Although China is also stepping up development, there are still certain limiting factors in the complete localization of bearing research and development. Most domestic sliding bearing manufacturers are still using traditional methods for production and have not yet solved the problem of replacing imported bearings.
[0003] In the Chinese patent with application number 201610712259.8, flame spraying technology is used to sequentially prepare soft and hard alternating composite coatings on the surface of the bearing material. The thickness of the Cu coating is 15-50μm, the thickness of the WC coating is 15-50μm, and the thickness of the MoS2 coating is 15-50μm, and the total thickness does not exceed 100μm. This soft and hard alternating composite coating consists of hard particles wrapped in a soft coating, and the hard coating improves the load-bearing capacity. There is a buffering effect between the coatings, which can effectively reduce and slow down the generation of cracks. The wear resistance and friction reduction performance of the bearing are improved, the bearing capacity of the bearing is improved, and the embedding performance of the bearing is improved, thereby improving the working life and anti-lock performance of the bearing. However, the coating structure prepared by this patent is strictly speaking "soft-hard-soft", and the data friction coefficient simulation results are excellent, but in actual applications, the role of the middle WC hard coating is not obvious, and the thermal expansion coefficients of the three coatings of Cu, WC and MoS2 are very different. The soft coating below the WC is prone to cracking under heavy load conditions, resulting in the inability to exert the excellent lubrication properties of the MoS2 coating above. The idea of "soft and hard" coating is good, but the coating selection, preparation technology selection and coating design selection still need to be improved; in addition, the preparation cost of this method is also very high and has no practical value.
[0004] In the Chinese patent with application number 201710879833.3, magnetron sputtering technology is used to prepare a composite coating of alternating layers of Ni transition layer, AlSn20Cu layer and Ag layer on the surface of steel / CuPb22Sn4 or steel / AlZn4SiPb bearing. This multi-layer design effectively relieves the stress of the coating, reduces the friction coefficient and wear rate, and enhances the anti-fatigue performance. However, the aluminum-tin-copper (AlSn20Cu) coating in the coating of this patent is not cutting-edge enough, and the tribological properties and anti-bite properties need to be improved. All coatings in this patent are prepared by magnetron sputtering, and are multi-layer superposition, which cannot guarantee excellent bonding strength. There is a certain gap in the hardness of the two types of coatings, and hardness mismatch is prone to occur.
[0005] In the Chinese patent with application number 202211348829.1, the electric spark alloying soft anti-friction coating process is used to prepare transition layers of Ag, Cu and Babbitt alloy coatings on the surface of the tin-bronze alloy bearing in sequence, which can effectively reduce the friction coefficient of the tin-bronze bearing surface and obtain a tin-bronze bearing with good surface comprehensive performance, excellent anti-friction performance, strong fatigue resistance, high reliability and good durability. However, the outermost layer of this patent is Babbitt alloy, which is an obsolete material, and the upper metal hardness is higher than the lower Ag and Cu metal hardness. The structure is "soft and hard", and the overall support layer is lacking. The bearing as a whole is prone to overall deformation under heavy load conditions, which seriously affects the working reliability and service life.
[0006] In the Chinese patent with application number 201210498063.5, an organic / inorganic composite coating containing a solid lubricating phase is prepared on a copper-based bearing by a spraying method. The coating mainly includes a mixture of molybdenum disulfide, graphite, hexagonal boron nitride, cerium trifluoride, antimony trioxide, silicone resin and some organic solvents. The problem of unsatisfactory lubrication performance, copper adhesion and insufficient wear resistance of traditional copper-based metal bearings is solved. However, the coating preparation method of the patent is a spraying method, which is very easy to fall off in actual working conditions, and the lubrication effect of the coating is extremely poor. It is not easy to work for a long time. After falling off, it will continue to contact the copper substrate, which is very easy to lock and seriously affect the service life. In addition, the coating contains organic solvents, which is not environmentally friendly. Summary of the invention
[0007] The present invention designs and develops a self-lubricating and anti-friction coating for a bearing based on a top layer of an Ag layer. The purpose of the present invention is to solve the problems of high friction coefficient, poor anti-seizure property and short service life of the alloy layer in the existing special bimetallic alloy bearing.
[0008] The present invention designs and develops a method for preparing a self-lubricating and anti-friction coating for a bearing based on a top layer of an Ag layer. The purpose of the present invention is to provide an advanced aluminum-tin-copper alloy (AlSn35Cu) supporting functional layer and an anti-friction self-lubricating layer with an Ag layer as the top layer during the preparation process, and the composite structure is a new type of anti-friction and lubricating bearing coating material. The introduction of the anti-friction and lubricating layer with an Ag layer as the top layer also further improves the wear resistance of the aluminum-tin-copper alloy (AlSn35Cu) supporting functional layer, and solves the problems of high friction coefficient, poor anti-seizure performance, and short service life of the alloy layer in the existing special bimetallic alloy bearing.
[0009] The present invention designs and develops an application of a self-lubricating and anti-friction coating for a bearing based on a top layer of an Ag layer. The purpose of the present invention is to solve the problems of high friction coefficient, poor anti-seizure property and short service life of the alloy layer in the bimetallic alloy bearing of a diesel engine.
[0010] The technical solution provided by the present invention is:
[0011] A method for preparing a self-lubricating anti-friction coating for a bearing bush based on a top layer of an Ag layer comprises the following steps:
[0012] Step 1: placing the pretreated metal substrate in a vacuum chamber of an ion beam assisted deposition device, setting the sputtering target to Ni, adjusting the argon gas flow, voltage and current, turning on the target arc power supply to deposit a Ni gate layer and then cooling it to form a transitional barrier layer;
[0013] Step 2: Replace the sputtering target with AlSn35Cu, adjust the argon gas flow, voltage and current, clean the surface of the transition barrier layer formed after cooling through a low-energy ion source, turn on the target arc power supply to deposit the AlSn35Cu layer, and form a supporting functional layer after cooling;
[0014] Step 3: Replace the sputtering target with Ag, adjust the argon gas flow, voltage and current, clean the surface of the support functional layer formed after cooling through a low-energy ion source, turn on the target arc power supply to deposit the Ag layer to form a friction-reducing self-lubricating layer, and obtain the self-lubricating and friction-reducing coating for the bearing based on the top layer of the Ag layer after cooling;
[0015] Wherein, in the step 2 and the step 3, during the deposition of the AlSn35Cu layer and the Ag layer, the sputtering target atoms are bombarded by a high energy ion source at the same time.
[0016] Preferably, in the step 1, the pretreatment process of the substrate includes: grinding the surface of the substrate with sandpaper, and then cleaning and drying it for standby use.
[0017] Preferably, in step 1, the sputtering conditions for depositing the Ni gate layer include: a sputtering time of 60 to 600 min, a sputtering voltage of 1000 V to 1200 V, a sputtering current of 0.7 A to 1.5 A, and a sputtering pressure of 1×10 -1 Pa.
[0018] Preferably, in the step 2, the cleaning conditions include: cleaning time of 5 minutes, main arc voltage of 10-25V, main arc current of 1.0-2.5A, extraction voltage of 1.0-2.5kV, extraction current of 50-150mA; and
[0019] In the step three, the cleaning conditions include: cleaning time is 10 minutes, main arc voltage is 30V, main arc current is 2.0A, extraction voltage is 1.5kV, and extraction current is 100mA.
[0020] Preferably, in the step 2, the sputtering conditions for depositing the AlSn35Cu layer include: a sputtering time of 120 to 1000 min, a sputtering voltage of 700 V to 1000 V, a sputtering current of 0.7 A to 1.2 A, and a sputtering pressure of 2 to 5×10 -1 Pa; and
[0021] In step 3, the sputtering conditions for depositing the Ag layer include: a sputtering time of 60 to 600 min, a sputtering voltage of 1000 V, a sputtering current of 1.1 A, and a sputtering pressure of 1×10 -1 Pa.
[0022] Preferably, the conditions for bombarding and sputtering the AlSn35Cu target with a high energy ion source include: a bombardment stage time of 20 min, a main arc voltage of 50-75 V, a main arc current of 2.0-2.5 A, an extraction voltage of 5 kV, an extraction current of 42 mA, an acceleration voltage of 42-58 kV, and an acceleration current of 8-16 mA; and
[0023] The conditions for the high energy ion source bombardment sputtering of the Ag target include: the bombardment stage time is 20 min, the main arc voltage is 50 V, the main arc current is 1.5 A, the extraction voltage is 5 kV, the extraction current is 52 mA, the acceleration voltage is 50 kV, and the acceleration current is 10 mA.
[0024] Preferably, the thickness of the Ni gate layer is 0.55-4.0 μm, the thickness of the AlSn35Cu layer is 2.8-15 μm, and the thickness of the Ag layer is 0.85-8.0 μm.
[0025] A self-lubricating and anti-friction coating for a bearing bush based on a top layer of Ag layer, prepared using the method for preparing the self-lubricating and anti-friction coating for a bearing bush based on a top layer of Ag layer, comprising a transition barrier layer, a supporting functional layer and an anti-friction self-lubricating layer deposited in sequence;
[0026] Wherein, the transition barrier layer comprises a Ni barrier layer, the supporting functional layer comprises a deposited AlSn35Cu layer, and the anti-friction self-lubricating layer comprises a deposited Ag layer.
[0027] Preferably, the thickness of the Ni gate layer is 0.55-4.0 μm, the thickness of the AlSn35Cu layer is 2.8-15 μm, and the thickness of the Ag layer is 0.85-8.0 μm.
[0028] The invention discloses an application of a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer in a bearing bush of a diesel engine. The self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer is used.
[0029] The beneficial effects of the present invention are:
[0030] 1. In the self-lubricating and anti-friction coating structure for bearing bushes based on the top layer of the Ag layer provided by the present invention, the AlSn35Cu coating is used as a supporting functional layer, which is a bearing material with excellent microstructure. Sn is relatively soft and is a soft component. Its content is relatively high, which is conducive to obtaining better running performance, such as compliance and as small a tendency to bite as possible. Al and Cu are relatively hard and are hard components, which can obtain good fatigue resistance. The coating is thick as a whole and has a certain hardness, has a certain supporting effect, and also has a certain lubricating property. The Ag coating has low shear strength, excellent self-lubricity, and excellent ductility, which enhances its embeddability, and further improves the anti-friction and anti-wear effect of the AlSn35Cu coating in actual working conditions.
[0031] 2. The copper alloy layer in the self-lubricating and anti-friction coating for bearings based on the top layer of the Ag layer provided by the present invention is CuNi2, the magnetron sputtered Ni transition layer has good bonding force, and the nickel-containing material itself has certain excellent friction and wear properties, and has great development prospects in the service environment actually required by the bearings; the AlSn35 coating is currently the leading component in the aluminum-tin-copper coating of the bearings. When the tin content increases, the hardness and fatigue strength of the aluminum-tin alloy decrease to a certain extent, but the bite, embedding and compliance increase accordingly, the anti-bite load increases accordingly, and the wear of the journal decreases accordingly; and as for the coating itself, under dry friction conditions, tin can form a protective film on the surface of the shaft to overcome the sharp changes in friction, and will not cause a sharp increase in the load in local areas of the bearings, and can better maintain the continuity of the lubricating oil film; the Ag coating, the Ag wear debris generated in actual service can be used as a lubricating oil additive to reduce friction and wear under start-stop conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the structure of the self-lubricating and anti-friction coating for the bearing bush based on the top layer of the Ag layer according to the present invention;
[0033] Figure 2 The present invention is a flow chart of a method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer;
[0034] Figure 3a The XRD spectrum of the substrate in the self-lubricating and anti-friction coating for bearing bushes based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0035] Figure 3b The XRD spectrum of the AlSn35Cu coating in the self-lubricating and anti-friction coating for the bearing bush based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0036] Figure 3c The XRD spectrum of the Ag coating in the self-lubricating and anti-friction coating for the bearing bush based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0037] Figure 4a This is a cross-sectional SEM morphology of the substrate in the self-lubricating and anti-friction coating for bearing bushes based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0038] Figure 4b This is an EDS spectrum of the substrate in the self-lubricating and anti-friction coating for bearing bushes based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0039] Figure 5a This is a cross-sectional SEM morphology of the self-lubricating and anti-friction coating for the bearing bush based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0040] Figure 5bThis is a cross-sectional EDS spectrum of the self-lubricating and anti-friction coating for a bearing bush based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0041] Figure 6 The friction coefficient curve of the self-lubricating anti-friction coating for the bearing bush based on the top layer of the Ag layer prepared in Example 1 of the present invention;
[0042] Figure 7 This is a surface SEM morphology of the self-lubricating and anti-friction coating for the bearing based on the top layer of the Ag layer prepared in Example 1 of the present invention after the friction test. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0044] like Figure 1 As shown, the present invention provides a self-lubricating and anti-friction coating for a bearing based on a top layer of an Ag layer, comprising: a transition barrier layer 120, a supporting functional layer 130 and an anti-friction self-lubricating layer 140 coated on a bimetallic substrate; wherein the bimetallic substrate comprises a steel backing layer 100 and a copper alloy layer 110, the transition barrier layer 120 specifically comprises a Ni barrier layer, the supporting functional layer 130 specifically comprises a deposited AlSn35Cu layer, and the anti-friction self-lubricating layer 140 specifically comprises a deposited Ag layer.
[0045] In another embodiment, the material of the steel backing layer 100 is carbon structural steel, and the material of the copper alloy layer 110 is copper-nickel alloy.
[0046] In another embodiment, the thickness of the Ni gate layer is 0.55-4.0 μm, the thickness of the AlSn35Cu layer is 2.8-15 μm, and the thickness of the Ag coating is 0.85-8.0 μm.
[0047] like Figure 2 As shown, the present invention provides a method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer, comprising the following steps:
[0048] Step S100, pretreatment of the bearing bimetal substrate: pretreatment of the bearing bimetal substrate to be processed, grinding and polishing the substrate surface to meet the requirements of magnetron sputtering and subsequent ion beam assisted deposition, and removing grease and impurities attached to the substrate surface;
[0049] Step S200, preparing the transition barrier layer 120: depositing a Ni barrier layer of 0.55-4.0 μm on the surface of the pre-treated bearing bimetallic substrate by magnetron sputtering;
[0050] Step S300, preparing AlSn35Cu coating 130: depositing a 2.8-15.0 μm supporting functional AlSn35Cu coating on the Ni gate layer of S200 by ion beam assisted deposition technology;
[0051] Step S400, preparing the anti-friction self-lubricating Ag coating 140: depositing a 0.85-8.0 μm anti-friction self-lubricating Ag coating on the AlSn35Cu layer of S300 by ion beam assisted deposition technology;
[0052] Step S500, finally sealing the sample of the self-lubricating anti-friction coating for the bearing based on the top layer of the Ag layer: after the Ni / AlSn35Cu / Ag composite coating is formed on the surface of the sample, it is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0053] In another embodiment, the specific process of step S100 may include:
[0054] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0055] Step S102, placing the polished bimetallic substrate of the bearing bush in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0056] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0057] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0058] Step S105, placing the substrate in a 100°C oven to dry for 20 minutes, then taking it out and wrapping it with dust-free paper for later use.
[0059] In another embodiment, the specific process of step S200 may include:
[0060] Step S201: The sample is mounted on a fixture and placed in a vacuum chamber of a magnetron sputtering device. Argon is introduced into the vacuum chamber as a protective gas. Before the sample is taken out, the argon gas should be continuously circulated, and the working pressure is 1×10 - 1 Pa, argon purity is 99.9%;
[0061] Step S202, depositing a Ni gate layer with a thickness of 0.55-4.0 μm on the surface of the sample by magnetron sputtering; the sputtering time is 60-600 min, the sputtering voltage is 1000 V-1200 V, and the sputtering current is 0.7 A-1.5 A;
[0062] Step S203: After the reaction is completed, wait for the sample to cool down in the furnace for 4 hours and then take out the sample;
[0063] In another embodiment, the specific process of step S300 may include:
[0064] Step S301: Mount the sample after magnetron sputtering on a fixture and place the whole in a vacuum chamber of an ion beam assisted deposition device. Fill the vacuum chamber with argon as a protective gas. Before taking out the sample, the argon should be continuously circulated, and its working pressure is 1.0-5.0×10 -1 Pa, argon purity is 99.9%;
[0065] Step S302, using a low-energy ion source to clean the sample surface, the process includes: the low-energy ion source is used to clean the sample surface for 5 minutes, wherein the main arc voltage is 10-25V, the main arc current is 1.0-2.5A, the extraction voltage is 1.0-2.5kV, and the extraction current is 50-150mA;
[0066] Step S303: deposit an AlSn35Cu coating with a thickness of 2.8 to 15.0 μm on the surface of the sample by magnetron sputtering; the sputtering time is 120 to 1000 min, the sputtering voltage is 700 V to 1000 V, the sputtering current is 0.7 A to 1.2 A, and the sputtering pressure is 2 to 5×10 -1 Pa;
[0067] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50-75V, the main arc current was 2.0-2.5A, the extraction voltage was 5kV, the extraction current was 42mA, the acceleration voltage was 42-58kV, and the acceleration current was 8-16mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the Ni layer for nucleation and growth, so as to improve the bonding force between the AlSn35Cu layer and the underlying Ni layer, and improve the overall deposition quality of the film layer.
[0068] Step S304: After the above steps are completed, the furnace is cooled to room temperature.
[0069] In another embodiment, the specific process of step S400 may include:
[0070] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0071] Step S402, using a low-energy ion source to clean the sample surface, the process includes: the low-energy ion source is used to clean the sample surface for 10 minutes, wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0072] Step S403: deposit a 0.85-8.0 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 60-600 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0073] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 120 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn35Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn35Cu layer below, and improve the overall deposition quality of the film layer.
[0074] Step S404: After the above steps are completed, the furnace is cooled to room temperature.
[0075] In another embodiment, the thickness of the Ni gate layer is 2.6-3.8 μm.
[0076] In another embodiment, the thickness of the AlSn35Cu coating is 5-12.2 μm.
[0077] In another embodiment, the thickness of the Ag coating is 2.0-4.8 μm.
[0078] The present invention will be further described below in conjunction with specific embodiments.
[0079] Example 1
[0080] The present invention provides a method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer, comprising the following steps:
[0081] Step S100: pretreatment of the bearing bimetal substrate:
[0082] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0083] Step S102, placing the polished bimetallic substrate of the bearing bush in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0084] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0085] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0086] Step S105, placing the substrate in a 100°C oven to dry for 20 minutes, then taking it out and wrapping it with dust-free paper for later use.
[0087] Step S200, depositing a 2.8 μm Ni grid layer on the surface of the pre-treated bearing bimetallic substrate by magnetron sputtering:
[0088] Step S201: The sample is mounted on a fixture and placed in a vacuum chamber of a magnetron sputtering device. Argon is introduced into the vacuum chamber as a protective gas. Before the sample is taken out, the argon gas should be continuously circulated, and the working pressure is 1.0×10 - 1 Pa, argon purity is 99.9%;
[0089] Step S202, depositing a Ni gate layer on the surface of the sample by magnetron sputtering; wherein the sputtering time is 240 min, the sputtering voltage is 1000 V to 1200 V, and the sputtering current is 0.7 A to 1.5 A;
[0090] Step S203: After the reaction is completed, wait for the sample to cool down in the furnace for 4 hours and then take out the sample;
[0091] Step S300, depositing a 11.3 μm supporting functional AlSn35Cu coating on the Ni layer of S200 by ion beam assisted deposition technology:
[0092] Step S301: Mount the sample after magnetron sputtering on a fixture and place the whole in a vacuum chamber of an ion beam assisted deposition device. Fill the vacuum chamber with argon as a protective gas. Before taking out the sample, the argon should be continuously circulated, and its working pressure is 1.0-5.0×10 -1 Pa, argon purity is 99.9%;
[0093] Step S302, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 5 minutes, wherein the main arc voltage is 10-25V, the main arc current is 1.0-2.5A, the extraction voltage is 1.0-2.5kV, and the extraction current is 50-150mA;
[0094] Step S303: depositing AlSn35Cu coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 350 min, the sputtering voltage is 700 V to 1000 V, the sputtering current is 0.7 A to 1.2 A, and the sputtering pressure is 2 to 5×10 -1 Pa;
[0095] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50-75V, the main arc current was 2.0-2.5A, the extraction voltage was 5kV, the extraction current was 42mA, the acceleration voltage was 42-58kV, and the acceleration current was 8-16mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the Ni layer for nucleation and growth, so as to improve the bonding force between the AlSn35Cu layer and the underlying Ni layer, and improve the overall deposition quality of the film layer.
[0096] Step S304: After the above steps are completed, the furnace is cooled to room temperature;
[0097] Step S400: Depositing a 2.0 μm self-lubricating Ag coating on the AlSn35Cu layer of S300 by ion beam assisted deposition technology:
[0098] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0099] Step S402, using a low-energy ion source to clean the sample surface. The low-energy ion source is used to clean the sample surface for 10 minutes, wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0100] Step S403: depositing an Ag coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 120 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0101] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups to obtain high energy, and finally accelerated to bombard the surface of the AlSn35Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn35Cu layer below, and improve the overall deposition quality of the film layer.
[0102] Step S404: After the above steps are completed, the sample is taken out after cooling to room temperature in the furnace;
[0103] Step S500, sealing the final sample, covering the sample with the Ni / AlSn35Cu / Ag composite coating formed on the surface with degreasing paper and dust-free paper, and then vacuum sealing and storing it.
[0104] Example 2
[0105] The present invention provides a method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer, comprising the following steps:
[0106] Step S100: pretreatment of the bearing bimetal substrate:
[0107] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0108] Step S102, placing the polished bimetallic substrate of the bearing bush in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, and then taking it out and wiping it clean with a clean silk cloth;
[0109] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0110] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0111] Step S105, placing the substrate in a 100°C oven to dry for 20 minutes, then taking it out and wrapping it with dust-free paper for later use.
[0112] Step S200, depositing a 0.55 μm Ni grid layer on the pre-treated surface of the bearing bimetallic substrate by magnetron sputtering:
[0113] Step S201: The sample is mounted on a fixture and placed in a vacuum chamber of a magnetron sputtering device. Argon is introduced into the vacuum chamber as a protective gas. Before the sample is taken out, the argon gas should be continuously circulated, and the working pressure is 1.0×10 - 1 Pa, argon purity is 99.9%;
[0114] Step S202, depositing a Ni gate layer on the surface of the sample by magnetron sputtering; wherein the sputtering time is 60 minutes, the sputtering voltage is 1000V to 1200V, and the sputtering current is 0.7A to 1.5A;
[0115] Step S203: After the reaction is completed, wait for the sample to cool down in the furnace for 4 hours and then take out the sample;
[0116] Step S300, depositing a 2.8 μm supporting functional AlSn35Cu coating on the Ni layer of S200 by ion beam assisted deposition technology:
[0117] Step S301: Mount the sample after magnetron sputtering on a fixture and place the whole in a vacuum chamber of an ion beam assisted deposition device. Fill the vacuum chamber with argon as a protective gas. Before taking out the sample, the argon should be continuously circulated, and its working pressure is 1.0-5.0×10 -1 Pa, argon purity is 99.9%;
[0118] Step S302, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 5 minutes, wherein the main arc voltage is 10-25V, the main arc current is 1.0-2.5A, the extraction voltage is 1.0-2.5kV, and the extraction current is 50-150mA;
[0119] Step S303: depositing AlSn35Cu coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 120 min, the sputtering voltage is 700 V to 1000 V, the sputtering current is 0.7 A to 1.2 A, and the sputtering pressure is 2 to 5×10 -1 Pa;
[0120] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50-75V, the main arc current was 2.0-2.5A, the extraction voltage was 5kV, the extraction current was 42mA, the acceleration voltage was 42-58kV, and the acceleration current was 8-16mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the Ni layer for nucleation and growth, so as to improve the bonding force between the AlSn35Cu layer and the underlying Ni layer, and improve the overall deposition quality of the film layer.
[0121] Step S304: After the above steps are completed, the furnace is cooled to room temperature;
[0122] Step S400: Depositing a 0.85 μm self-lubricating Ag coating on the AlSn35Cu layer of S300 by ion beam assisted deposition technology:
[0123] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0124] Step S402, using a low-energy ion source to clean the sample surface. The low-energy ion source is used to clean the sample surface for 10 minutes, wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0125] Step S403: depositing an Ag coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 60 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0126] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups to obtain high energy, and finally accelerated to bombard the surface of the AlSn35Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn35Cu layer below, and improve the overall deposition quality of the film layer.
[0127] Step S404: After the above steps are completed, the sample is taken out after cooling to room temperature in the furnace;
[0128] Step S500, sealing the final sample, covering the sample with the Ni / AlSn35Cu / Ag composite coating formed on the surface with degreasing paper and dust-free paper, and then vacuum sealing and storing it.
[0129] Example 3
[0130] The present invention provides a method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer, comprising the following steps:
[0131] Step S100: pretreatment of the bearing bimetal substrate:
[0132] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0133] Step S102, placing the polished bimetallic substrate of the bearing bush in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, and then taking it out and wiping it clean with a clean silk cloth;
[0134] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0135] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0136] Step S105, placing the substrate in a 100°C oven to dry for 20 minutes, then taking it out and wrapping it with dust-free paper for later use.
[0137] Step S200, depositing a 3.8 μm Ni grid layer on the surface of the pre-treated bearing bimetallic substrate by magnetron sputtering:
[0138] Step S201: The sample is mounted on a fixture and placed in a vacuum chamber of a magnetron sputtering device. Argon is introduced into the vacuum chamber as a protective gas. Before the sample is taken out, the argon gas should be continuously circulated, and the working pressure is 1.0×10 - 1 Pa, argon purity is 99.9%;
[0139] Step S202, depositing a Ni gate layer on the surface of the sample by magnetron sputtering; wherein the sputtering time is 480 min, the sputtering voltage is 1000 V to 1200 V, and the sputtering current is 0.7 A to 1.5 A;
[0140] Step S203: After the reaction is completed, wait for the sample to cool down in the furnace for 4 hours and then take out the sample;
[0141] Step S300, depositing a 12.2 μm supporting functional AlSn35Cu coating on the Ni layer of S200 by ion beam assisted deposition technology:
[0142] Step S301: Mount the sample after magnetron sputtering on a fixture and place the whole in a vacuum chamber of an ion beam assisted deposition device. Fill the vacuum chamber with argon as a protective gas. Before taking out the sample, the argon should be continuously circulated, and its working pressure is 1.0-5.0×10 -1 Pa, argon purity is 99.9%;
[0143] Step S302, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 5 minutes, wherein the main arc voltage is 10-25V, the main arc current is 1.0-2.5A, the extraction voltage is 1.0-2.5kV, and the extraction current is 50-150mA;
[0144] Step S303: depositing AlSn35Cu coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 700 min, the sputtering voltage is 700 V to 1000 V, the sputtering current is 0.7 A to 1.2 A, and the sputtering pressure is 2 to 5×10 -1 Pa;
[0145] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50-75V, the main arc current was 2.0-2.5A, the extraction voltage was 5kV, the extraction current was 42mA, the acceleration voltage was 42-58kV, and the acceleration current was 8-16mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the Ni layer for nucleation and growth, so as to improve the bonding force between the AlSn35Cu layer and the underlying Ni layer, and improve the overall deposition quality of the film layer.
[0146] Step S304: After the above steps are completed, the furnace is cooled to room temperature;
[0147] Step S400: Depositing a 3.8 μm self-lubricating Ag coating on the AlSn35Cu layer of S300 by ion beam assisted deposition technology:
[0148] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0149] Step S402, using a low-energy ion source to clean the sample surface. The low-energy ion source is used to clean the sample surface for 10 minutes, wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0150] Step S403: depositing an Ag coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 240 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0151] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups to obtain high energy, and finally accelerated to bombard the surface of the AlSn35Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn35Cu layer below, and improve the overall deposition quality of the film layer.
[0152] Step S404: After the above steps are completed, the sample is taken out after cooling to room temperature in the furnace;
[0153] Step S500, sealing the final sample, covering the sample with the Ni / AlSn35Cu / Ag composite coating formed on the surface with degreasing paper and dust-free paper, and then vacuum sealing and storing it.
[0154] Example 4
[0155] The present invention provides a method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer, comprising the following steps:
[0156] Step S100: pretreatment of the bearing bimetal substrate:
[0157] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0158] Step S102, placing the polished bimetallic substrate of the bearing bush in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, and then taking it out and wiping it clean with a clean silk cloth;
[0159] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0160] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0161] Step S105, placing the substrate in a 100°C oven to dry for 20 minutes, then taking it out and wrapping it with dust-free paper for later use.
[0162] Step S200, depositing a 2.6 μm Ni grid layer on the surface of the pre-treated bearing bimetallic substrate by magnetron sputtering:
[0163] Step S201: The sample is mounted on a fixture and placed in a vacuum chamber of a magnetron sputtering device. Argon is introduced into the vacuum chamber as a protective gas. Before the sample is taken out, the argon gas should be continuously circulated, and the working pressure is 1.0×10 - 1 Pa, argon purity is 99.9%;
[0164] Step S202, depositing a Ni gate layer on the surface of the sample by magnetron sputtering; wherein the sputtering time is 360 min, the sputtering voltage is 1000 V to 1200 V, and the sputtering current is 0.7 A to 1.5 A;
[0165] Step S203: After the reaction is completed, wait for the sample to cool down in the furnace for 4 hours and then take out the sample;
[0166] Step S300, depositing a 5 μm supporting functional AlSn35Cu coating on the Ni layer of S200 by ion beam assisted deposition technology:
[0167] Step S301: Mount the sample after magnetron sputtering on a fixture and place the whole in a vacuum chamber of an ion beam assisted deposition device. Fill the vacuum chamber with argon as a protective gas. Before taking out the sample, the argon should be continuously circulated, and its working pressure is 1.0-5.0×10 -1 Pa, argon purity is 99.9%;
[0168] Step S302, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 5 minutes, wherein the main arc voltage is 10-25V, the main arc current is 1.0-2.5A, the extraction voltage is 1.0-2.5kV, and the extraction current is 50-150mA;
[0169] Step S303: depositing AlSn35Cu coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 720 min, the sputtering voltage is 700 V to 1000 V, the sputtering current is 0.7 A to 1.2 A, and the sputtering pressure is 2 to 5×10 -1 Pa;
[0170] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50-75V, the main arc current was 2.0-2.5A, the extraction voltage was 5kV, the extraction current was 42mA, the acceleration voltage was 42-58kV, and the acceleration current was 8-16mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the Ni layer for nucleation and growth, so as to improve the bonding force between the AlSn35Cu layer and the underlying Ni layer, and improve the overall deposition quality of the film layer.
[0171] Step S304: After the above steps are completed, the furnace is cooled to room temperature;
[0172] Step S400: Depositing a 4.8 μm self-lubricating Ag coating on the AlSn35Cu layer of S300 by ion beam assisted deposition technology:
[0173] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0174] Step S402, using a low-energy ion source to clean the sample surface. The low-energy ion source is used to clean the sample surface for 10 minutes, wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0175] Step S403: depositing an Ag coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 480 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0176] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups to obtain high energy, and finally accelerated to bombard the surface of the AlSn35Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn35Cu layer below, and improve the overall deposition quality of the film layer.
[0177] Step S404: After the above steps are completed, the sample is taken out after cooling to room temperature in the furnace;
[0178] Step S500, sealing the final sample, covering the sample with the Ni / AlSn35Cu / Ag composite coating formed on the surface with degreasing paper and dust-free paper, and then vacuum sealing and storing it.
[0179] Example 5
[0180] The present invention provides a method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer, comprising the following steps:
[0181] Step S100: pretreatment of the bearing bimetal substrate:
[0182] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0183] Step S102, placing the polished bimetallic substrate of the bearing bush in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0184] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0185] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0186] Step S105, placing the substrate in a 100°C oven to dry for 20 minutes, then taking it out and wrapping it with dust-free paper for later use.
[0187] Step S200, depositing a 4 μm Ni grid layer on the surface of the pre-treated bearing bimetallic substrate by magnetron sputtering:
[0188] Step S201: The sample is mounted on a fixture and placed in a vacuum chamber of a magnetron sputtering device. Argon is introduced into the vacuum chamber as a protective gas. Before the sample is taken out, the argon gas should be continuously circulated, and the working pressure is 1.0×10 - 1 Pa, argon purity is 99.9%;
[0189] Step S202, depositing a Ni gate layer on the surface of the sample by magnetron sputtering; wherein the sputtering time is 600 min, the sputtering voltage is 1000 V to 1200 V, and the sputtering current is 0.7 A to 1.5 A;
[0190] Step S203: After the reaction is completed, wait for the sample to cool down in the furnace for 4 hours and then take out the sample;
[0191] Step S300, depositing a 15 μm supporting functional AlSn35Cu coating on the Ni layer of S200 by ion beam assisted deposition technology:
[0192] Step S301: Mount the sample after magnetron sputtering on a fixture and place the whole in a vacuum chamber of an ion beam assisted deposition device. Fill the vacuum chamber with argon as a protective gas. Before taking out the sample, the argon should be continuously circulated, and its working pressure is 1.0-5.0×10 -1 Pa, argon purity is 99.9%;
[0193] Step S302, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 5 minutes, wherein the main arc voltage is 10-25V, the main arc current is 1.0-2.5A, the extraction voltage is 1.0-2.5kV, and the extraction current is 50-150mA;
[0194] Step S303: depositing AlSn35Cu coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 1000 min, the sputtering voltage is 700 V to 1000 V, the sputtering current is 0.7 A to 1.2 A, and the sputtering pressure is 2 to 5×10 -1 Pa;
[0195] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50-75V, the main arc current was 2.0-2.5A, the extraction voltage was 5kV, the extraction current was 42mA, the acceleration voltage was 42-58kV, and the acceleration current was 8-16mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the Ni layer for nucleation and growth, so as to improve the bonding force between the AlSn35Cu layer and the underlying Ni layer, and improve the overall deposition quality of the film layer.
[0196] Step S304: After the above steps are completed, the furnace is cooled to room temperature;
[0197] Step S400, depositing an 8 μm self-lubricating Ag coating on the AlSn35Cu layer of S300 by ion beam assisted deposition technology:
[0198] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0199] Step S402, using a low-energy ion source to clean the sample surface. The low-energy ion source is used to clean the sample surface for 10 minutes, wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0200] Step S403: depositing an Ag coating on the surface of the sample by magnetron sputtering; wherein the sputtering time is 600 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0201] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 20 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups to obtain high energy, and finally accelerated to bombard the surface of the AlSn35Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn35Cu layer below, and improve the overall deposition quality of the film layer.
[0202] Step S404: After the above steps are completed, the sample is taken out after cooling to room temperature in the furnace;
[0203] Step S500, sealing the final sample, covering the sample with the Ni / AlSn35Cu / Ag composite coating formed on the surface with degreasing paper and dust-free paper, and then vacuum sealing and storing it.
[0204] Test Case
[0205] In the present invention, by adjusting the sputtering time during the deposition of the Ni gate layer, the deposition of the AlSn35Cu layer and the deposition of the Ag layer, and adjusting the thickness of the Ni gate layer, the AlSn35Cu layer and the Ag layer, a coating material with a lower friction coefficient can be obtained. The test example is as follows:
[0206] The bearing samples in Example 1 were taken for SEM, friction and wear, and optical microscopy testing and characterization: the equipment model of the optical microscope was DM6000M, the equipment model of the scanning electron microscope was SU5000, and the equipment model of the friction and wear testing machine was MS-T3000; wherein, when the friction and wear analysis of the samples was performed by the friction and wear tester, the friction and wear tester was preheated for 20 minutes at room temperature, the same air humidity and oil lubrication environment, and the test was performed under the oil lubrication test conditions of Φ5mm sliding distance, 15N load, 200r / min rotation speed, and 60min test time.
[0207] As shown in Figure 3, Figure 3b , Figure 3c As shown, Figure 3a It is a bimetallic alloy substrate, the outermost layer is mainly copper alloy, and its XRD spectrum is composed of the diffraction peak of Cu phase (PDF#85-1326); the XRD spectrum of AlSn35Cu coating is mainly composed of the diffraction peaks of Sn phase (PDF#86-2265) and Al phase (PDF#85-1527) in addition to the diffraction peak of Cu phase; the XRD spectrum of Ag coating is composed of the diffraction peak of Ag phase (PDF#87-0597).
[0208] like Figure 4a , Figure 4bAs shown in the figure, there is a clear boundary between the steel back layer and the copper alloy layer under the scanning electron microscope and EDS surface scanning state. After measurement, the average thickness of the copper alloy layer is 548.0μm.
[0209] like Figure 5a , Figure 5b As shown in the figure, the dividing line between the three coatings is quite obvious. The average thickness of the top Ag coating is 2.0μm. This layer mainly plays a self-lubricating role, reduces the friction coefficient, and wraps the hard particles generated on the outside or during the friction and wear process. The average thickness of the second top AlSn35Cu coating is 11.3μm. This layer will play a major role in friction and wear, so it is thicker. The average thickness of the bottom Ni layer is 2.8μm.
[0210] like Figure 6 As shown, the friction and wear analysis of the bearing coating surface was carried out by a friction and wear tester. The friction and wear tester was preheated for 20 minutes at room temperature and air humidity, and the test was carried out under the test conditions of oil lubrication, high load and high speed. The friction coefficient was at an extremely low level at the beginning. After 60 minutes of testing, the average friction coefficient was extremely low, only 0.08.
[0211] like Figure 7 As shown, the width of the wear scar is only about 410μm, the wear scar surface is relatively smooth, and no obvious failure phenomena such as biting occur. The friction and wear test in Example 1 was maintained for 60 minutes, and the average friction coefficient was 0.08; the friction and wear test in Example 2 was maintained for 20 minutes, and the friction coefficient rose rapidly. The coating was too thin as a whole and failed quickly under high speed and high load; the friction and wear test in Example 3 was maintained for 60 minutes, and the average friction coefficient remained at 0.11; the average friction coefficient in Example 4 was maintained at 0.10; the average friction coefficient in Example 5 was maintained at 0.09; the above examples can prove that the self-lubricating anti-friction coating for bearings based on the top layer of the Ag layer provided by the present invention can significantly reduce the friction coefficient, has good anti-biting performance, reduces the risk of locking, and improves the service life and reliability in work.
[0212] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of Ag, characterized in that: The steps include: Step 1: placing the pretreated metal substrate in a vacuum chamber of an ion beam assisted deposition device, setting the sputtering target to Ni, adjusting the argon gas flow, voltage and current, turning on the target arc power supply to deposit a Ni gate layer and then cooling it to form a transitional barrier layer; Step 2: Replace the sputtering target with AlSn35Cu, adjust the argon gas flow, voltage and current, clean the surface of the transition barrier layer formed after cooling through a low-energy ion source, turn on the target arc power supply to deposit the AlSn35Cu layer, and form a supporting functional layer after cooling; Step 3: Replace the sputtering target with Ag, adjust the argon gas flow, voltage and current, clean the surface of the support functional layer formed after cooling through a low-energy ion source, turn on the target arc power supply to deposit the Ag layer to form a friction-reducing self-lubricating layer, and obtain the self-lubricating and friction-reducing coating for the bearing based on the top layer of the Ag layer after cooling; Wherein, in the step 2 and the step 3, during the deposition of the AlSn35Cu layer and the Ag layer, the sputtering target atoms are bombarded by a high energy ion source at the same time.
2. The method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of Ag as claimed in claim 1, characterized in that: In the step 1, the pretreatment process of the substrate includes: grinding the surface of the substrate with sandpaper, and then cleaning and drying it for standby use.
3. The method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of an Ag layer as claimed in claim 1 or 2, characterized in that: In the step 1, the sputtering conditions for depositing the Ni gate layer include: a sputtering time of 60 to 600 min, a sputtering voltage of 1000 V to 1200 V, a sputtering current of 0.7 A to 1.5 A, and a sputtering pressure of 1×10 -1 Pa.
4. The method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of Ag as claimed in claim 1, characterized in that: In the step 2, the cleaning conditions include: cleaning time of 5 minutes, main arc voltage of 10-25V, main arc current of 1.0-2.5A, extraction voltage of 1.0-2.5kV, extraction current of 50-150mA; and In the step three, the cleaning conditions include: cleaning time is 10 minutes, main arc voltage is 30V, main arc current is 2.0A, extraction voltage is 1.5kV, and extraction current is 100mA.
5. The method for preparing a self-lubricating anti-friction coating for a bearing bush based on a top layer of Ag as claimed in claim 4, characterized in that: In the step 2, the sputtering conditions for depositing the AlSn35Cu layer include: a sputtering time of 120 to 1000 min, a sputtering voltage of 700 V to 1000 V, a sputtering current of 0.7 A to 1.2 A, and a sputtering pressure of 2 to 5×10 -1 Pa; and In step 3, the sputtering conditions for depositing the Ag layer include: a sputtering time of 60 to 600 min, a sputtering voltage of 1000 V, a sputtering current of 1.1 A, and a sputtering pressure of 1×10 -1 Pa.
6. The method for preparing a self-lubricating anti-friction coating for a bearing bush based on a top layer of Ag as claimed in claim 5, characterized in that: The conditions for the high energy ion source bombardment sputtering of AlSn35Cu target material include: bombardment stage time of 20 minutes, main arc voltage of 50-75V, main arc current of 2.0-2.5A, extraction voltage of 5kV, extraction current of 42mA, acceleration voltage of 42-58kV, acceleration current of 8-16mA; and The conditions for the high energy ion source bombardment sputtering of the Ag target include: the bombardment stage time is 20 min, the main arc voltage is 50 V, the main arc current is 1.5 A, the extraction voltage is 5 kV, the extraction current is 52 mA, the acceleration voltage is 50 kV, and the acceleration current is 10 mA.
7. The method for preparing a self-lubricating and anti-friction coating for a bearing bush based on a top layer of Ag as claimed in any one of claims 1, 2, 4-6, characterized in that: The thickness of the Ni gate layer is 0.55-4.0 μm, the thickness of the AlSn35Cu layer is 2.8-15 μm, and the thickness of the Ag layer is 0.85-8.0 μm.
8. A self-lubricating anti-friction coating for a bearing bush based on a top layer of Ag, characterized in that: The self-lubricating and anti-friction coating for the bearing bush based on the Ag top layer is prepared by the method for preparing the self-lubricating and anti-friction coating for the bearing bush according to any one of claims 1 to 7, comprising a transition barrier layer, a supporting functional layer and an anti-friction and self-lubricating layer deposited in sequence; Wherein, the transition barrier layer comprises a Ni barrier layer, the supporting functional layer comprises a deposited AlSn35Cu layer, and the anti-friction self-lubricating layer comprises a deposited Ag layer.
9. The self-lubricating anti-friction coating for bearing bushes based on the top layer of Ag as claimed in claim 8, characterized in that: The thickness of the Ni gate layer is 0.55-4.0 μm, the thickness of the AlSn35Cu layer is 2.8-15 μm, and the thickness of the Ag layer is 0.85-8.0 μm.
10. Application of a self-lubricating anti-friction coating for a bearing bush based on a top layer of Ag layer in a bearing bush of a diesel engine, characterized in that: Use of the self-lubricating anti-friction coating for bearing bushes based on the Ag top layer as claimed in claim 8.
Citation Information
Patent Citations
Method for preparing solid lubricant coating on copper base bearing bush
CN103849311A
Alternating Hard and Soft Composite Coating for Bearing Material Surface and its Preparation Method
CN106222656B
All-metal self-lubricating and friction-reducing coating for bearing bushes and its preparation method
CN107699859B
Tin bronze bearing bush surface electric spark alloying soft antifriction coating process
CN115679319A